Penerapan Model Project Based Learning Berbantuan Media ChemOnDro untuk Meningkatkan Hasil Belajar Siswa Kelas XI pada Materi Sistem Koloid - Wa Ode Saputry Ningrat; Saefuddin; Yuniati Tewa (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2024)
This study aims to determine student’ responses and compare student’s learning outcomes using ChemOnDro media with a project based learning model and students with a direct learning model on colloidal system material. The population of study is all 11th grade class students and the sample selection taken by random sampling technique. This study applied a quasi experimental design. The research instrument consists of questionnaires filled out by students and written tests consisting of pre-test and post-test. The results of data analysis of pretest scores obtained an average value of 13.625 and an average postest value of 82.31, these values have reached KKM. The response of students in the category was very good, with the average percentage of 86.65%. Based on the t test, we get the sig value. (2-tailed) 0.00 ˂ 0.05 so it can be concluded that there is a significant difference between the control class and the experimental class.